McCune-Albright syndrome - A case report with transmission electron microscopy - Victor Garcia Neto; Hiram Larangeira de Almeida Jr; Claúdia Fernandes Lorea; Valéria Magalhães Jorge; Antônia Larangeira de Almeida (Sociedade Brasileira de Dermatologia, 2022)
Abstract McCune - Albright syndrome is a genetic disease with cutaneous mosaicism caused by post-zygotic activating mutations in GNAS locus, it has a triad of fibrous bone dysplasia, café-au-lait macules and precocious puberty. We examined a 22-year-old female patient with café au lait spot in right side of the abdomen, with a chessboard - like distribution, extending to right thigh with geographical contours, she has also an ovarian cyst, scoliosis and truncal obesity. Biopsies were taken from the hyperpigmented area and processed for light microscopy and for transmission electron microscopy. Light microscopy showed increased melanin pigment with HE staining. Immunohistochemistry with melanocytic markers (HMB-45 and Melan-A) revealed a normal number of melanocytes. Transmission electron microscopy demonstrated normal epidermal structures, such as desmosomes, cytokeratin filaments and hemidesmosomes. With high magnifications an irregular melanossomal contour was seen, with some indentations in their outline.